PENINGKATAN KETERAMPILAN DAN KEAHLIAN STAF MELALUI PENDIDIKAN DAN PELATIHAN DI BAGIAN AKADEMIK FAKULTAS MIPA UNIVERSITAS MULAWARMAN SAMARINDA - Paini Nurningsih (Jurnal Paradigma (JP), 2017)
Skill and expertise improvement of academic staff through education and training in Faculty of Mathematic and Natural Science Mulawarman University has succeded, but it doesn’t bring any changes to the middle skill employee.  The existing skill and expetise improvement contribute significantly for supporting employee performance in order to achieve the persistent vision and mission. There is a better change to employee who is ever  joint the education and training. Its contribution not only for improving the skill it self, but it also becomes the institutional investment for solving the problem in the future.